Chromospheric thermodynamic conditions from inversions of complex Mg II h & k profiles observed in flares - Sainz Dalda, Alberto; De Pontieu, Bart (Frontiers in Astronomy and Space Sciences, 2023)
The flare activity of the Sun has been studied for decades, using both space- and ground-based telescopes. The former have mainly focused on the corona, while the latter have mostly been used to investigate the conditions in the chromosphere and photosphere. The Interface Region Imaging Spectrograph (IRIS) instrument has served as a gateway between these two cases, given its capability to observe quasi-simultaneously the corona, the transition region, and the chromosphere using different spectral lines in the near- and far-ultraviolet ranges. IRIS thus provides unique diagnostics to investigate the thermodynamics of flares in the solar atmosphere. In particular, the Mg II h&k and Mg II UV triplet lines provide key information about the thermodynamics of low to upper chromosphere, while the C II 1334 & 1335 Å lines cover the upper-chromosphere and low transition region. The Mg II h&k and Mg II UV triplet lines show a peculiar, pointy shape before and during the flare activity. The physical interpretation, i.e., the physical conditions in the chromosphere, that can explain these profiles has remained elusive. In this paper, we show the results of a non-LTE inversion of such peculiar profiles. To better constrain the atmospheric conditions, the Mg II h&k lines and the Mg II UV triplet lines are simultaneously inverted with the C II 1334 & 1335 Å lines. This combined inversion leads to more accurate derived thermodynamic parameters, especially the temperature and the turbulent motions (micro-turbulence velocity). We use an iterative process that looks for the best fit between the observed profile and a synthetic profile obtained by considering non-local thermodynamic equilibrium and partial frequency redistribution of the radiation due to scattered photons. This method is computationally rather expensive (≈ 6CPU −hour/profile). Therefore, we use the k-means clustering technique to identify representative profiles and associated representative model atmospheres. By inverting the representative profiles with the most advanced inversion code (STiC), in addition to recover the main physical paramteres, we are able to conclude that these unique, pointy profiles are associated with a large gradient in the line-of-sight velocity along the optical depth in the high chromosphere.